Pengaruh Kepercayaan Merek Dan Label Halal Terhadap Keputusan Pembelian Produk Skincare Halal Pada Generasi Z Di Indonesia - Inayah Fadhila; Rini Rahmadani; Rahmat Hidayat Siregar; Hafiz Maulana Siregar; Zainarti Zainarti (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study was motivated by the increasing interest of Generation Z in Indonesia in halal skincare products, Skincare Store on IAIN Street, Medan, which not only offers functional benefits, but also guarantees safety, cleanliness, and compatibility with the values they hold. This study aims to describe in depth how brand trust and halal labels influence the purchasing decisions of two skincare products that are currently popular among young consumers, namely Dörskin Pink Bliss Moisturizer and Glad2Glow Cherry Blossom Betaine Micellar Water. Using a qualitative descriptive method, data was collected through in-depth interviews with active users of both products, observations of halal skincare usage experiences, and analysis of digital reviews on social media, which serves as the primary reference platform, for Generation Z. The research findings indicate that brand trust acts as an initial factor in building consumer confidence before they decide to purchase. This trust is formed from several important aspects, including a positive brand image on social media, numerous authentic testimonials and reviews from other users, transparency from the manufacturer in communicating ingredient content, and consistent quality in product results. Dörskin and Glad2Glow are viewed as credible brands because they offer products that are safe, effective, and tailored to the needs of teenage and young adult skin..